Social Service Providers’ Understanding of the Consequences of Human Trafficking on Women Survivors—A South African Perspective - Sipho Sibanda; Juliet Sambo; Sanjeev Dahal (Social Sciences)
Human trafficking for forced labour or sexual exploitation often takes the form of forced migration. It is the third-largest crime industry in the world and has severe consequences on the women survivors. Trafficking violates the safety, welfare, and human rights of the victims and forces physical and psychological imprisonment on them. Despite the significant number of women being trafficked, little is known about the best ways to address their needs. This article highlights the understanding developed by social service providers in South Africa regarding the consequences of human trafficking on women survivors. Being aware of the complex challenges faced by women survivors of human trafficking enables social service providers to respond to their needs effectively through appropriate interventions and services. Data for this qualitative study were collected through one-on-one interviews and analysed using thematic analysis. Social service providers understand the following to be related to women survivors of trafficking: involvement in drugs and sex work, dependency on the perpetrator, lack of self-esteem, self-blame and shame, being disoriented, psychological challenges, lack of financial support, health issues, isolation, and loneliness. To be relevant and effective, services should be packaged in a manner that addresses all the challenges faced by women survivors of human trafficking.